2020
DOI: 10.3390/su122410281
|View full text |Cite
|
Sign up to set email alerts
|

Other- versus Self-Referenced Social Impacts of Events: Validating a New Scale

Abstract: Publicly funded sport events are partially justified based on positive social impacts. Past research generally measured social impact for a generic and global “other” with claims such as “Events create new friendships in the community”. These other-referenced (OR) social impacts are generally higher pre-event than post-event and are inflated for both methodological and theoretical reasons. In the pre-event period of the Tokyo 2020 Olympic and Paralympic Games, we empirically tested OR items compared to self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 60 publications
(143 reference statements)
1
29
0
Order By: Relevance
“…Second, this study adopted a means-end theory to explain wheelchair basketball spectators' perceived social impacts, exploring how individuals choose products or services to fulfill their desires; this has a potential relationship with the consumer decision-making process. Previous research showed that perceived social impacts are estimated primarily when items are questioned using other-referenced rather than self-referenced measures; however, such research did not identify a theory to underpin this explanation (Taks et al , 2020). Therefore, this study adopted the means-end theory for wheelchair basketball spectators, and the cultural/educational value perceived from spectating wheelchair basketball is expected to be stronger than community benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, this study adopted a means-end theory to explain wheelchair basketball spectators' perceived social impacts, exploring how individuals choose products or services to fulfill their desires; this has a potential relationship with the consumer decision-making process. Previous research showed that perceived social impacts are estimated primarily when items are questioned using other-referenced rather than self-referenced measures; however, such research did not identify a theory to underpin this explanation (Taks et al , 2020). Therefore, this study adopted the means-end theory for wheelchair basketball spectators, and the cultural/educational value perceived from spectating wheelchair basketball is expected to be stronger than community benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Taks et al (2020) suggested changing the points of reference (other-referenced versus self-referenced) when measuring social impacts for sport events. However, they did not identify any theory to explain why self-referenced measures would underestimate reality than other-referenced measures.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Social exchange theory is one of the most popular theories adapted to social impact studies [22]. The rationale behind this theory is to describe the behavioural interactions between two or more individuals and how these behavioural interactions reinforce the other's behaviour, which actors, on this basis, would exchange benefits for both [23].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…All items introduced were written in English and translated to Japanese; two native speakers checked translation validity. Since the social impacts were measured a year before the mega-sporting event, the items were worded in the future tense, using the self-referenced [22,55].…”
Section: Measurements Scalementioning
confidence: 99%